Tourists, lard and pork greaves. Interculturality and food practices in baixo alentejo - Piedade, Ana (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2023)
The aim of this paper is to think how food practices of a region are transformed into a tourist product and, more specifically, how the poor food of Baixo Alentejo, often considered as “non-food”, is valued in the restaurants at the beginning of 21st century. We will consider the case of Serpa, a town known for the traditional food practices that are still maintained and the quality offered by its restaurants. Besides, it is an attractive region for tourists, mainly Portuguese and Spanish, who, on weekends, cross the border to try “typical” and traditional food of the region.